2014
DOI: 10.1186/s13612-014-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences in psychological and affective well-being between physicians and resident physicians: Does high and low self-regulation capacity matter?

Abstract: Background: Physician well-being has rapidly become an important area of interest given that reduced well-being can have a negative effect on patient outcomes. The majority of studies in this area have focused on impairment, and research on skills and processes that allow physicians and resident physicians to achieve and maintain adequate levels of well-being has been limited. As such, the purpose of the present study was to adopt a positive psychology approach to investigate well-being as more than the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…34 Other studies involving medical school students have also reported a positive association between leisure activities and SWB scores, 35 as well as a negative association between leisure activities and stress levels 1,36 ; such reality also includes the elderly and the young population in general. 37 It is possible that higher and physicians, [38][39][40] with medical students' perception about the need to balance work and lifestyle, 41 and with their perception about social support. 42 Previous studies involving the medical population have also evidenced decreased happiness associated with lower sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…34 Other studies involving medical school students have also reported a positive association between leisure activities and SWB scores, 35 as well as a negative association between leisure activities and stress levels 1,36 ; such reality also includes the elderly and the young population in general. 37 It is possible that higher and physicians, [38][39][40] with medical students' perception about the need to balance work and lifestyle, 41 and with their perception about social support. 42 Previous studies involving the medical population have also evidenced decreased happiness associated with lower sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large number of studies on physicians' job satisfaction (Lichtenstein, 1984 ; Cooper et al, 1989 ; Konrad et al, 1999 ; Williams et al, 1999 ; Lavanchy et al, 2004 ; Bell et al, 2006 ; Etchegaray et al, 2010 ; Mcintyre and Mcintyre, 2010 ; Hann et al, 2011 ; Mohr and Burgess, 2011 ; Jönsson, 2012 ; Bouwkamp-Memmer et al, 2013 ) and well-being (Firth-Cozens, 2001 ; Arnetz et al, 2002 ; Wallace and Lemaire, 2007 ; Janisse, 2008 ; Fang et al, 2011 ; Hills et al, 2012 ; Rockey, 2012 ; Alsuwaida et al, 2013 ; Bell, 2013 ; Aalto et al, 2014 ; Heponiemi et al, 2014 ; Simon and Durand-Bush, 2014 ; Min et al, 2015 ; Scheepers et al, 2015 ; Tucker et al, 2015 ), there is apparently little interest in physicians' dissatisfaction and its roots.…”
Section: Introductionmentioning
confidence: 99%
“…21 It has furthermore been implemented in the general population as well as among physicians and residents as a tool to study affect and well-being in relation to clinical performance. [24][25][26][27]…”
Section: Vey (Edes)mentioning
confidence: 99%